1983
DOI: 10.1007/bf00008126
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary organic carbon budget for a small dystrophic lake in Maritime Canada

Abstract: The results of a preliminary organic budget for a small (1.13 h) dystrophic lake in Maritime Canada are presented. Wood's Pond is moderately autotrophically productive (395 mg C m-2 day-'). Allochthonous inputs overwhelmed autochthonous production by an approximate ratio of 9.7:1. Seepage through the surrounding Sphagnum mosses accounted for 89.9% of all organic carbon entering the lake while fluvial transport was responsible for over 90% of losses. The yearly balance was a net loss of approximately 1 820 kg C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Statistically also relationship was observed to exist between pH and DOC on one hand and DOC and temperature on the other (Figs. 3 & 4) with correlation coefficients of -0.649 and -0.59 respectively which is in agreement with the results of Carpenter et al (1983).…”
Section: Discussionsupporting
confidence: 81%
“…Statistically also relationship was observed to exist between pH and DOC on one hand and DOC and temperature on the other (Figs. 3 & 4) with correlation coefficients of -0.649 and -0.59 respectively which is in agreement with the results of Carpenter et al (1983).…”
Section: Discussionsupporting
confidence: 81%
“…Across the full dataset, mean DOCout/DOCin was 0.70 (standard deviation 0. 31 were highly significant between oligotrophic and eutrophic sites (p < 0.001), and between mesotrophic and eutrophic sites (p = 0.004), but non-significant between oligotrophic and mesotrophic sites (p = 0.23). Regardless of whether sites were net DOC sources or sinks, the overall rate and magnitude of DOC change was strongly influenced by WRT.…”
Section: Figure 1 Relationships Between Docout/docin and Wrt For Watmentioning
confidence: 93%
“…For lakes with multiple sampled inflows [DOC]in was calculated by weighting the mean concentrations of each inflow according to either gauged water discharge for each inflow (if reported) or alternatively according to subcatchment area. Although DOC input to waterbodies can occur through direct precipitation to the water surface, most studies that measured this flux found that it only contributed a few percent of the total DOC input 31,32 . Because few studies reported rainfall fluxed, we assumed a zero DOC input via this pathway in all studies.…”
Section: Implications For Aquatic Carbon Cyclingmentioning
confidence: 99%
“…Net primary production (NPP) was measured monthly at Stations I, II and III using the lightedark bottle method and Winkler oxygen analysis (APHA, 1995). In some studies primary production was considered in the carbon input (Carpenter et al, 1983;Quay et al, 1986). By taking up gaseous CO 2 the phytoplankton has an active role in creating concentration difference between the lake surface and the atmosphere, which is crucial for CO 2 influx.…”
Section: Overall Mass Balancementioning
confidence: 99%
“…Previous carbon budget studies in northern temperate mesotrophic and dystrophic lakes, using an overall mass balance method, where CH 4 was not taken into account, showed that lakes could be a carbon source (Carpenter et al, 1983) or carbon sink (Cole et al, 1989;Eadie and Robertson, 1976). Carbon budget studies using a gas exchange and carbon burial balance showed the ratio of gaseous carbon exchange across the watereair interface of most northern temperate lakes to be greater than 1, similar to the average global ratio for lakes which is also greater than 1 indicating that most lakes are a carbon source (Algesten et al, 2004;Cole and Caraco, 1998;Dillon and Molot, 1997;Hanson et al, 2004) (Table 3).…”
Section: Comparison Of Carbon Source/sink Functions Of Lake Donghu Tomentioning
confidence: 99%